Factibilidad para desarrollar un plan de negocio dedicado a la adaptación y comercialización de ciclomotores, con diseño especial para discapacitados en la ciudad de Cali (2011)
The accomplishment of the project tries to satisfy and give solution to the problematic of self mobilize that daily live the people with disabilities in the city of Cali, offering the opportunity to people who have some difficulty to walk that they can have means of own transport bringing them independence and security. The objective is to constitute the Comodidad Al Alcance S.A.S. whose business plan is destined to the adaptation and commercialization of mopeds with special design and 23 reasonable prices in the city of Cali, for people with physical limitations in the inferior extremities, contributing to improve its quality of life. In order to obtain the fulfillment of the objectives of this project, it refers to the use of field investigation techniques, basing in a survey made to a determined percentage of people who fulfill with the requirements of age, disability, and considering all socioeconomic sectors, in addition information is obtained through DANE statistics It will achieved that this important sector of the Cali city population acquire mopeds on reasonable prices, additionally this new idea of business will generate direct job opportunities to this population. They will be able to evolve in the construction of the moped participating in these processes; in Cali very few companies hire personnel with physical limitations.